The Role of E-Commerce Platforms in Resolving Breach of Contract Disputes Related to the Delivery of Goods Not in Accordance with Consumer Orders by Business Actors - Fikri, Muhammad; Sugiyono, Heru (Law Development Journal, 2025)
This research discusses the role of e-commerce platforms in resolving default disputes in e-commerce transactions with a focus on the case of delivery of goods not according to order as the object of research. The purpose of this research is to analyze the effectiveness of legal protection for consumers as well as the role of the platform in resolving such disputes. This research uses normative juridical method with statutory approach and case study. The results show that although there is a legal basis in the form of the Consumer Protection Law and its implementing regulations, implementation in the field is still not optimal. The obstacles faced include low consumer legal literacy, lack of transparency in the dispute resolution mechanism in the platform, and the lack of connection between the platform's internal system and the official dispute resolution institution. In addition, e-commerce platforms have not fully carried out their responsibilities as organizers of the digital transaction ecosystem. This research concludes that strategic steps are needed in the form of strengthening regulations, integrating dispute resolution systems with official institutions, and increasing legal education for consumers in order to create a fair, fast and sustainable dispute resolution mechanism.